2015
DOI: 10.1007/s10877-015-9707-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the time-dependent need for stay in a high dependency unit (HDU) after major surgery by using data from an anesthesia information management system

Abstract: Admittance to a high dependency unit (HDU) is expensive. Patients who receive surgical treatment with 'low anterior resection of the rectum' (LAR) or 'abdominoperineal resection of the rectum' (APR) at our hospital are routinely treated in an HDU the first 16-24 h of the postoperative (PO) period. The aim of this study was to describe the extent of HDU-specific interventions given. We included patients treated with LAR or APR at the St. Olav University Hospital (Trondheim, Norway) over a 1-year period. Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A study from Aberdeen looking at 128 patients who had airway surgery in the otolaryngology unit concluded that the care provided in the HDU prevented the need for escalation of care to an intensive care unit. The authors suggested that this challenges the need for patient management on intensive care units following major surgery or airway compromise for those not requiring assisted ventilation [13].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Aberdeen looking at 128 patients who had airway surgery in the otolaryngology unit concluded that the care provided in the HDU prevented the need for escalation of care to an intensive care unit. The authors suggested that this challenges the need for patient management on intensive care units following major surgery or airway compromise for those not requiring assisted ventilation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was the association between heart rate recovery 1, HRR‐AUC and distance achieved at 6MWT, with cardiopulmonary complications 30 days after surgery as defined by the European Society of Thoracic Surgeons ‘Silver‐book’ definitions [6]. Duration of HDU stay was explored as a secondary outcome, with prolonged stay defined as > 24 h postoperatively [7].…”
Section: Figurementioning
confidence: 99%
“…In addition, SDS can facilitate collaboration between technology and care providers through context-aware support for decision-making throughout the surgical care pathway. Examples of a data science approach to support decision support in surgical care include predicting the need for intensive care after major surgery [89], risk of highly consequential postoperative complications such as SSIs [46], [47], readmission after cardiac surgery [90], and reoperation or death after surgery for aortic aneurysm repair [91]. Predictive analytics in these studies relied on preoperative patient descriptors, intraoperative data, and postoperative variables (e.g.…”
Section: Examples and Potential Applicationsmentioning
confidence: 99%